What I wish I'd learned as an orthodontic trainee: an online survey of British Orthodontic Society members concerning postgraduate training experiences. (June 2020) - Oliver, Graham R; Lynch, Christopher D; Fleming, Padhraig S
Objective: To survey the opinion of recently qualified and established orthodontists on the perceived value of their training and to identify specific areas which which were considered to be deficient, adequately covered or focussed on excessively. Design: Descriptive cross-sectional survey Setting: Online electronic questionnaire. Participants: Members of the British Orthodontic Society (BOS). Methods: An electronic questionnaire was circulated to members of the BOS focusing on dental education history, and opinions concerning orthodontic teaching generally and specific clinical and non-clinical subjects. Information was also obtained in terms of possible need for improvement, modification or removal of teaching on focused academic and clinical aspects. Results: A total of 217 responses were received from 1080 emailed invitations resulting in a response rate of 20.1%. Respondents were generally satisfied with their training both in relation to theoretical, academic and practical aspects. However, training was regarded as deficient by some respondents in respect of temporary anchorage devices (38%), bonded retainers (6%), experience with lingual appliances (47%), removable aligners (44%), inter-proximal reduction (24%) and adult orthodontics (16%), working with therapists (32%), and NHS contracts (47%) and commissioning (47%). Conclusion: The overall satisfaction of BOS members with postgraduate orthodontic training is generally high, although both recently qualified and established practitioners emphasised the need for better exposure to training in specific practical aspects and practice management within the NHS.